Analisa Penerapan Deret Hitung (Arithmatic Series) sebagai Model untuk Menentukan Kecepatan Pengemasan Biscuit Gabin Lido Samarinda, Kaltim - Rudzali, Achmad; Sampeallo, Yulius Gessong; Patabang, Lewi; Cahyono, Aris Tri; Iswanti, Aurel Sabrina (Politeknik Negeri Samarinda, 2024)
Understanding the subject matter in the course is very important Especially in teaching for the Samarinda state polytechnic or POLNES Not only are they required to understand or understand, but graduates are required to be able and these habits should be able to be applied to daily community activities One of the courses taught at POLNES majoring in accounting is business mathematics The object of this business mathematics research is the legendary gabin bread business in Samarinda. Observations and data recording were carried out randomly per week for 3 months Collecting data on the speed of wrapping or packaging gabin bread products carried out by 8 old employees and 3 new employees Data were analyzed through statistics, arithmetic series models and other mathematical models The results obtained are the average speed of wrapping gabin bread is 72 packs, while the new employees are 42 packs The average speed of wrapping 72 packs for new employees is estimated to be approximately 22 days after they start working In the equality model if the production is around 693 packs per day and 1 employee is absent, then the company is equivalent to employing 7 old employees and 5 new employees Through graphic analysis, it is concluded that employee turnover is recommended for no more than 5 people in a certain period Through the model if there is a problem in production, through the reverse comparison model, the company can only produce a maximum of 630 or 91% of the target average packaging per day.